FAKTOR- FAKTOR YANG BERASOSIASI PADA KEJADIAN STUNTING PADA BAYI DI BAWAH DUA TAHUN DI WILAYAH KERJA PUSKESMAS PANDRAH KABUPATEN BIREUEN - Fitriani, Aida; Gurnida, Dida A.; Rachmawati, Anita (Care : Jurnal Ilmiah Ilmu Kesehatan, 2020)
Stunting is a condition of physical growth failure characterized by height for age under -2 SD from the WHOchart growth standard. This study used adesign cross sectional with variables of birth weight, non-exclusive breastfeeding, maternal education, education. father, history of ANC visits, socio-economic history, and work history of parents.  This study used a sample of 56 baduta who were stunting. The sample in this study, namely mothers who have baduta. This study uses instruments in the form of a questionnaire and an infantometer. Data analysis used univariable analysis, bivariable analysis with chi square test and multivariable with logistic regression analysis.  The results showed that the prevalence of stunting in the study site was 31.8%, the factor most associated with stunting in the ANC visit was POR = 10.54 (95% CI: 4.20-25.03) p value =